Finding Potential Therapeutic Targets against Shigella flexneri through Proteome Exploration - Hossain, Mohammad Uzzal; Khan, Md. Arif; Hashem, Abu; Islam, Md. Monirul; Morshed, Mohammad Neaz; Keya, Chaman Ara; Salimullah, Md. (Frontiers in Microbiology, 2016)
Abstract: Background: Shigella flexneri is a gram negative bacteria that causes the infectious disease ‘shigellosis’. Shigella flexneri (S. flexneri) is responsible for developing diarrhea, fever and stomach cramps in human. Antibiotics are mostly given to patients infected with shigella. Resistance to antibiotics can hinder its treatment significantly. Upon identification of essential therapeutic targets, vaccine and drug could be effective therapy for the treatment of shigellosis. Methods: The study was designed for the identification and qualitative characterization for potential drug targets from S. flexneri by using the subtractive genome analysis. A set of computational tools were used to identify essential proteins those are required for the survival of S. flexneri. Total proteome (13503 proteins) of S. flexneri was retrieved from NCBI and further analyzed by subtractive channel analysis. After identification of the metabolic proteins we have also performed its qualitative characterization to pave the way for the identification of promising drug targets. Results: Subtractive analysis revealed that a list of 53 targets of S. flexneri were human non-homologous essential metabolic proteins that might be used for potential drug targets. We have also found that 11 drug targets are involved in unique pathway. Most of these proteins are cytoplasmic, can be used as broad spectrum drug targets, can interact with other proteins and show the druggable properties. The functionality and drug binding site analysis suggest a promising effective way to design the new drugs against S. flexneri. Conclusion: We have identified 13 potential novel drug and one vaccine target(s) against S. flexneri. The outcome might also be used as module as well as circuit design in systems biology. Keywords: S. flexneri, drug target, therapeutics, metabolic proteins, proteome